Epithelial Membrane Protein 1 is a Potential Prognostic Biomarker for Ovarian Cancer - Yongjin Xie; Zhen Huang; Zhiwei Chen; Yingying Lin (IMR Press, 2022)
Background: Epithelial membrane protein 1 (EMP1) is a cell junction protein located in the plasma membrane. The function of EMP1 in cancer cells varies in different tumour types. In the present study we investigated the expression of EMP1 and its clinical significance in ovarian cancer. Methods: Sequencing data from the Cancer Genome Atlas (TCGA) and from several other public databases was used to study the expression of EMP1 and its gene regulation networks in ovarian cancer patients. Oncomine and Gene Expression Profiling Interactive Analysis tools (GEPIA) were used to evaluate EMP1 expression. EMP1 alterations were identified using cBioPortal and the prognostic value of EMP1 was assessed using Kaplan-Meier analysis and OncoLnc online tools. Genes that were co-expressed with EMP1 were identified using LinkedOmics and the Link-Interpreter module was used to analyse pathway enrichment and the possible functions of co-expressed genes. Results: EMP1 was highly expressed in ovarian cancer and was associated with advanced tumour stage and poor overall survival (OS). Amplification of the EMP1 gene was also common in ovarian cancer. EMP1 participates mainly in the biological processes of epidermal development, cell adhesion, peptidyl tyrosine modification and angiogenesis. Functional network analysis suggests that EMP1 regulates tumorigenesis and progression of ovarian cancer through different signalling pathways that include several kinases, microRNAs (miRNAs) and transcription factors related to tumorigenesis. Conclusions: This study confirmed the expression of EMP1 in ovarian cancer and elucidated its regulatory networks, thus providing a theoretical basis for further studies into its functions. EMP1 could potentially serve as a diagnostic and prognostic biomarker in ovarian cancer patients. However, owing to the limited sample size and range of experimental work, further validation studies are needed to confirm the role of EMP1 in ovarian cancer.